Effect of solvent volume on the physical properties of spray deposited nano needle structured Sn2S3 thin films. (6th June 2016) - Prabha, D.; Ilangovan, S.; Nagarethinam, V.S.; Balu, A.R.
Abstract : Nanostructured Sn2 S3 thin films were deposited by spray pyrolysis technique from spraying solution having different values of solvent volume (10, 20, 30 and 40 ml) on glass substrates maintained at 400 °C. XRD studies showed that all the films exhibit orthorhombic crystal structure with a (2 1 1) preferential orientation. SEM images reveal that the Sn2 S3 films prepared from higher solvent volumes exhibited uniformly distributed nanoneedled grains. The optical band gap was blue shifted from 2.06 to 2.21 eV with increase in solvent volume. The photoluminescence spectra endorsed the lesser defect crystalline nature of the as-deposited Sn2 S3 films. The obtained results infer that the film coated with 30 ml solvent volume exhibited better physical properties.